Pembentukan Produk Unggulan Sebagai Pemberdayaan Kelompok Nelayan “Kub Sari Laut”, Desa Banjar Kemuning Kecamatan Sedati, Sidoarjo - Farida Hardaningrum Hardaningrum; Putri Zanufa Sari; Diah Ayu Restuti (Journal of Innovation and Applied Technology, 2020)
Where in this program offers several solutions including practicing the method of providing socialization about the importance of financial management of groups and people. For this, an inventory of all fishermen's data is held, and the next method is to consume shells into processed products in packaging that are ready to be marketed and have an acute selling power (contemporary bean shells “KERCHIP”). With the hope that the fishermen group in the village of Banjar Kemuning can be more careful in managing finances, and for the fishermen's wife to have the ability to manage shells enhancing a product with a better sale value